Enhancing visitation to KPTM library through marketing of the library service / Nurul Aliim Qadhijah Muhammad Shaiti - Muhammad Shaiti, Nurul Aliim Qadhijah (2013)
‘Perpustakaan Ibnu Sina II’ (KAMPUS LEMBAH SIREH) is faced with many challenges to maintain the library’s consumer retention. Besides, ‘Perpustakaan Ibnu Sina II’ should implement the right marketing strategy in order to attract attention to its visitors in KPTM to be interested to come frequently to the library to encourage people to be bookworm. Thus, this study has been conducted to enhance visitation to Kolej Poly-Tech Mara Kota Bharu library through marketing of the library service. A set of questionnaires was distributed to the respondent randomly. Several factors that being discussed in this research are public relation, promotion and product. The data is analyzed using descriptive analysis, reliability, correlation and regression analysis by using Statistical Package for Social Science (SPSS). Besides that, regression analysis was used to test the hypotheses in this study. In this research, the finding shows that public relation and product are significant to visiting KPTM library. Meanwhile, promotion was found to be insignificant to visiting KPTM library. Based on the results obtained, there are some suggested recommendations that can help Kolej Poly-Tech Mara Kota Bharu to enhance visitation to KPTM library through marketing of the library service.